(2r-13)-1(-6r+4)=

Simple and best practice solution for (2r-13)-1(-6r+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2r-13)-1(-6r+4)= equation:


Simplifying
(2r + -13) + -1(-6r + 4) = 0

Reorder the terms:
(-13 + 2r) + -1(-6r + 4) = 0

Remove parenthesis around (-13 + 2r)
-13 + 2r + -1(-6r + 4) = 0

Reorder the terms:
-13 + 2r + -1(4 + -6r) = 0
-13 + 2r + (4 * -1 + -6r * -1) = 0
-13 + 2r + (-4 + 6r) = 0

Reorder the terms:
-13 + -4 + 2r + 6r = 0

Combine like terms: -13 + -4 = -17
-17 + 2r + 6r = 0

Combine like terms: 2r + 6r = 8r
-17 + 8r = 0

Solving
-17 + 8r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 8r = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 8r = 0 + 17
8r = 0 + 17

Combine like terms: 0 + 17 = 17
8r = 17

Divide each side by '8'.
r = 2.125

Simplifying
r = 2.125

See similar equations:

| 4(4b-4)=4b+68 | | 3(2w+4)=3(6+2w) | | (y^3-y^2senx-x)dx+(3xy^2+2ycosx)dy=0 | | 15+2x=-5 | | ln(x+6)=ln(8x-5) | | 20x+5=5y | | (t-7)2=(t+7)2+168 | | -2(7+-2y)+3y=14 | | y^2-y+4=0 | | 4k^2-5=207 | | 8x-3x+2-x=x+x | | 13.4x=2.6x | | .5x=9-.5x | | 7x-19=-23+6x | | 15s^2-24s=63 | | y-5=7x | | 3r-7=-1+r | | 167=6+7(2+7r) | | (2x-3)(3x-4)-(x-13)(x-4)=40 | | y^2-y=28 | | 12=512+4 | | b^2-3b=88 | | x+5(5+2)+x-3(4+9)= | | 11x+35+90=90 | | 2x^2-8x+16=10 | | 11x+35+90=180 | | (5x+4)(x+3)=0 | | .75x+.05(18-x)=.10(-117) | | 49b^2-5=-1 | | (r-2)(r+7)=9 | | -20t+10=6 | | 18h^2+33h=-5 |

Equations solver categories